Understanding generational differences in digital skills and recreational behaviour for effective visitor management in forest destinations - Fruzsina Stefán; Mariusz Ciesielski; Andreas Weber; Kamil Choromański; Dariusz Gotlib; Karolina Taczanowska (Scientific Reports)
Abstract Digitalisation is reshaping how people interact with natural environments, particularly in the context of outdoor recreation. This study examines generational differences in digital skills and recreational behaviour and their implications for visitor management in urban forests. Based on an online panel survey conducted in the Vienna metropolitan area (n = 3,121), we identified four distinct visitor profiles using Self-Organizing Maps: All-rounders (49.6%), Traditional Planners and Navigators (17.2%), Tech-Savvy Navigators (14.5%), and Balanced Adapters (18.7%). These clusters differ in both digital competence and used information sources used for planning and navigating forest visits. Significant relationships were found between generational groups and visitor profiles: older adults (Baby Boomers, Traditionalists) were featured more prominently among Traditional Planners, while younger generations (Generation Z, Millennials) were more prevalent in the Tech-Savvy group. Balanced Adapters included older individuals transitioning towards digital tool use. Further, our findings highlight that younger users reported less frequent forest visits than older cohorts. These insights underscore the need for inclusive, hybrid infrastructure and communication strategies that address varying recreational needs, including trip planning and navigation behaviours. This study contributes to forest management and nearby recreation planning by revealing a generational gap in technology use in digitally evolving societies.